2008
DOI: 10.1161/circheartfailure.107.755504
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic, Hormonal, and Renal Actions of Adrenomedullin 2 in Experimental Heart Failure

Abstract: Background-Adrenomedullin 2 (AM2) is a novel member of the calcitonin gene-related peptide family that is thought to play a regulatory role in circulatory homeostasis under normal physiological conditions. The effects of AM2 in heart failure have not been investigated previously. Despite the increase in renin activity, plasma aldosterone levels were not significantly altered, whereas the aldosterone/plasma renin activity ratio was reduced (Pϭ0.08). Plasma vasopressin, endothelin-1, and catecholamines levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 51 publications
4
13
2
Order By: Relevance
“…Although the mechanisms underlying these renal actions of AM5 are yet to be established, it is possible that an increase in glomerular filtration may have contributed in light of the accompanying rise in creatinine clearance, as well as the observed decrease in circulating aldosterone levels. A similar enhancement of renal function has been demonstrated previously following identical doses of AM and AM2 in experimental ovine HF [11,12] (Table 2), with modes of action reported to include reductions in renal vascular resistance and increases in renal blood flow (via pre- and post-glomerular arteriolar vasodilation) and glomerular filtration rate, together with inhibition of proximal and distal fractional sodium reabsorption [37,39,40]. Similar direct actions of AM5 in the kidney might also be a possibility given the significant increase in urine cAMP levels.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although the mechanisms underlying these renal actions of AM5 are yet to be established, it is possible that an increase in glomerular filtration may have contributed in light of the accompanying rise in creatinine clearance, as well as the observed decrease in circulating aldosterone levels. A similar enhancement of renal function has been demonstrated previously following identical doses of AM and AM2 in experimental ovine HF [11,12] (Table 2), with modes of action reported to include reductions in renal vascular resistance and increases in renal blood flow (via pre- and post-glomerular arteriolar vasodilation) and glomerular filtration rate, together with inhibition of proximal and distal fractional sodium reabsorption [37,39,40]. Similar direct actions of AM5 in the kidney might also be a possibility given the significant increase in urine cAMP levels.…”
Section: Discussionsupporting
confidence: 81%
“…Although this effect is probably attributable in part to the attendant reduction in cardiac afterload (evidenced by falls in CTPR and MAP), it is plausible that AM5 also exhibits positive inotropic activity as the rise in CO was associated with prominent increases in LV d P /d t (max). Similar increases in CO and d P /d t (max) have been observed with AM and AM2 administration (Table 2) (in conjunction with enhanced coronary artery perfusion flow) [11,12,27], and both peptides are reported to have direct inotropic actions in isolated perfused rat hearts [8,9]. The AM5-induced rise in CO in the present study presumably contributed to the fall in LAP, although it is also possible that AM5 possesses venodilator actions as has been demonstrated for AM2 [28].…”
Section: Discussionsupporting
confidence: 61%
“…In addition, AM2/ IMD had no suppressive effects on aldosterone response to angiotensin II in conscious sheep in contrast to AM (Charles et al 2010). In experimental heart failure sheep, however, plasma aldosterone levels were not significantly altered during the infusion of human AM2/IMD 1-47 despite the increase in renin activity, and therefore, the aldosterone/ plasma renin activity ratio was reduced (Rademaker et al 2008). Thus, AM2/IMD may have a relative inhibition of angiotensin II induced aldosterone secretion in heart failure.…”
Section: Effects Of Adrenomedullin 2/intermedin On the Adrenal Hormonmentioning
confidence: 81%
“…6,7 We have previously reported the hemodynamic, hormonal, and renal actions of AM-2 in both normal conscious sheep 8 and sheep with pacinginduced heart failure. 9 These studies showed that AM-2 (as with AM) has favorable effects on cardiovascular, endocrine, and renal indices in heart failure and identify the peptide as a potential therapeutic target in this disease.…”
Section: Introductionmentioning
confidence: 99%